Perlindungan hak konsumen dalam perspektif HAM: Penipuan dalam transaksi e-commerce - Najah, Inayatin (Maliki Interdisciplinary Journal, 2026)
The development of e-commerce in the digital era has provided many conveniences in trade activities, but it has also created risks of fraud that can harm consumers. This study aims to examine consumer rights protection from the perspective of Human Rights (HAM), the factors causing fraud in electronic transactions, and the legal efforts available for victims of online fraud. The research method used is a qualitative method with a descriptive approach through literature review from various journals, books, and laws related to consumer protection and electronic transactions. The results show that consumer rights are part of human rights that must be protected, especially the rights to security, comfort, accurate information, and legal protection in digital transactions. E-commerce fraud is influenced by the low level of public digital literacy, weak supervision, and rapid technological development that is not balanced with adequate security systems. Legal protection for victims of fraud can be carried out through preventive and repressive measures, including strengthening regulations, public education, and law enforcement based on Consumer Protection Law and the Electronic Information and Transactions Law. Therefore, cooperation between the government, law enforcement agencies, digital platforms, and society is essential to create safe e-commerce transactions and protect consumer rights in the digital era.